2019
DOI: 10.1007/s40097-019-00323-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of PbS nanowires doped with Tb3+ ions by using chemical bath deposition method

Abstract: Crystalline lead sulfide (PbS) nanowires doped with terbium (Tb 3+) ions were synthesized by the chemical bath deposition method at room temperature. The powder was obtained from an aqueous solutions using lead acetate dehydrate, terbium nitrate, thiourea, potassium hydroxide and ammonia. The terbium molar concentrations were varied in the deposition process to investigate the effect on the structural, optical, morphological and luminescent properties of PbS nanowires. The crystalline size was found to be depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…From the figure, it is observed that the bandgap energy of all the films is 2.0 eV except for the films deposited with the 0.05 M and 0.15 M concentrations of Mn 2+ whose values decreased to 1.9 eV each. Similar result of bandgap tunning to the values in this range in addition to high absorbance values for the thin films of PbS doped with rare earth element (terbium -Tb) have also been "reported by [30]". This tunned range of bandgap values for the deposited thin films of PbMnS is within the solar spectrum (UV-VIS regions) and are thus ideal materials for solar cell applications for solar energy harnessing and development.…”
Section: Optical Properties Of the As Deposited (Pbmns) Thin Filmssupporting
confidence: 81%
“…From the figure, it is observed that the bandgap energy of all the films is 2.0 eV except for the films deposited with the 0.05 M and 0.15 M concentrations of Mn 2+ whose values decreased to 1.9 eV each. Similar result of bandgap tunning to the values in this range in addition to high absorbance values for the thin films of PbS doped with rare earth element (terbium -Tb) have also been "reported by [30]". This tunned range of bandgap values for the deposited thin films of PbMnS is within the solar spectrum (UV-VIS regions) and are thus ideal materials for solar cell applications for solar energy harnessing and development.…”
Section: Optical Properties Of the As Deposited (Pbmns) Thin Filmssupporting
confidence: 81%
“…The Raman spectra of the PLD-PbS films ( Figure 5 a) revealed several resolved bands. The broad bands peaking at 200 cm −1 , 437 cm −1 , and 630 cm −1 are related to the first, second, and third harmonics of the longitudinal optical (LO) phonon mode, respectively [ 46 , 47 ]. The line peaking at 520 cm −1 corresponds to the first-order optical phonon of the underlying silicon substrate [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…CBD has become one of the most widely used methods by virtue of its advantages of good controllability, uniformity, low cost and simple technology. [66][67][68][69] CBD is a technique for preparing semiconductors by immersing substrates such as glass or quartz in precursor solutions containing metal cations, anions, and chelating agents, allowing cations and anions to rst bind and then deposit on the substrate. 31,70,71 The synthesis of TiO 2 /CdS/MoS 2 ternary heterojunction nanorods was studied by Jang.…”
Section: Synthesis Methods Of 1d Cds Heterojunctionsmentioning
confidence: 99%